Actually existing silk roads. Issue 1 (2017) - Marsden, Magnus
This article explores the relevance of the concept of Silk Road for understanding the patterns of trade and exchange between China, Eurasia and the Middle East. It is based on ethnographic fieldwork in the city of Yiwu, in China's Zhejiang Province. Yiwu is a node in the global distribution of Chinese 'small commodities' and home to merchants and traders from across Asia and beyond. The article explores the role played by traders from Afghanistan in connecting the city of Yiwu to markets and trading posts in the world beyond. It seeks to bring attention to the diverse types of networks involved in such forms of trade, as well as their emergence and development over the past thirty years.